Management of major agricultural trauma in teenage boy: Case report - Marius Siksnius; Inga Dekeryte; Arturas Kilda; Robertas Bagdzevicius; Ausra Lukosiute-Urboniene (Elsevier, 2023)
We describe a case report of a teenage boy who fell into the straw pellets machine. Despite the major agricultural injuries to all his body and internal organs, the patient lives a good quality life. Even though it is a success story, high agricultural injury related mortality and morbidity rates persist in children. Mostly it is high energy and unclean injuries demanding initial fast assessment and challenging management. For the best possible outcome, it is important to follow the advanced trauma life support (ATLS) guidelines and do not understate the importance of early rehabilitation.